A Comprehensive Taxonomy for Serious Games. (September 2017) - De Lope, Rafael Prieto; Medina-Medina, Nuria
This article highlights the importance of establishing comprehensive taxonomies in the booming sector of serious games. Although various authors have proposed partial classification systems in this field, very little has so far been published on serious game taxonomies which serve to classify any type of serious game. This article proposes a comprehensive serious game taxonomy. The aim of this taxonomy is to gather the particular features of video game design and development, the platforms used to run the games, and operational aspects such as use, users, and distribution by highlighting the idiosyncrasies of the serious component. To this end, 16 criteria are discussed in this work. The taxonomy collects a large number of features that will be useful for those looking for a serious game (e.g., to teach a subject or train a skill). If they wish to use an existing game, the taxonomy helps to choose between the different options. If they need to develop a custom game, the taxonomy details the design alternatives to consider. The proposal has been applied on 22 serious games, and some interesting conclusions are drawn from this study. In addition, a web application has been built to support the proposal.